Building a DC electric field-driven wheat leaf-like surface pattern with a cholesteric liquid crystal fluoropolymer for directional droplet manipulation. Issue 19 (12th August 2022) - Li, Deyan; Mai, Zhijian; Feng, Yancong; Min, Hui; Liao, Jinglun; Wang, Yao; Li, Hao; Zhou, Guofu
Abstract : A wheat leaf-like surface pattern emerged above the solid coating of fluorinated cholesteric liquid crystal polymer under actuation of one-side DC electric field, to trigger directional droplet motion for precise and low-energy droplet manipulation. Abstract : As the most common natural act, precise manipulation of directional droplet motion has widely been mimicked for fabricating smart materials and devices. In this work, we built a direct current (DC) electric field-driven preconfigured surface pattern with a fluorinated cholesteric liquid crystal polymer. This solid pattern could be actuated by a one-side DC electric field (field strength threshold: 1.67 V μm −1 ), along with the emergence of a visible wheat leaf-like topography (maximum deformation index: 10%). Simultaneously, these patterned embossments rendered the coating surface hydrophobic enough to trigger the directional motion of water droplets on account of the wettability variation, weakened contact angle hysteresis, and drainage effect. This study presents a facile and practical strategy for constructing solid patterns for precise and low-energy droplet manipulation.